Automating the identification of opportunities for business process improvement patterns application. (2017) - Souza, Alexandre; Azevedo, Leonardo Guerreiro; Santoro, Flavia Maria
Business process management is increasingly present in organisations, and process improvement is one of its focuses. Patterns for process redesign provide solutions for recurring problems in business process improvement initiatives. However, choosing which patterns to apply in a process is not an easy task, especially in large and complex processes scenarios. This paper proposes heuristics to automate the process redesign pattern selection. The heuristics indicates specific process parts to apply improvement patterns, considering the business process model elements. A case study was performed to evaluate the proposal. The results highlight the applicability and reliability of heuristics to identify improvement opportunities in business processes models.